Progress and potential of genetic susceptibility to environmental toxicants - Haugen, A. (Scandinavian Journal of Work, Environment & Health, 1999)
Gene-environment interactions are thought to be critical for such multifactorial diseases as cancer diabetes, heart disease, asthma, and some neurological disorders. The genetic constitution of an individual (genotype) may influence the risk of disease of a person expsosed to environmental or occupational insults. Major advances will occur in the coming years with respect to the identification of the genetic and molecular causes of susceptibility to mutations and polymorphisms and in functional genomics. These rapid advances in genetics present new and complex ethical issues for both the individual and society.
Keywords: gene-environment interaction; microchip; molecular epidemiology; polymorphism; single-nucleotide polymorpism